Biotemplated CdS Nano-Aggregate Networks for Highly Effective Visible-Light Photocatalytic Hydrogen Production - Jiao He; Hongli Zhou; Guo Xiao; Yongjuan Chen; Zhiying Yan; Jiaqiang Wang (Nanomaterials, 2022)
In the last few decades, many new synthesis techniques have been developed in order to obtain an effective visible-light responsive photocatalyst for hydrogen production by water splitting. Among these new approaches, the biotemplated synthesis method has aroused much attention because of its unique advantages in preparing materials with special morphology and structure. In this work, Hydrilla verticillata (L. f.) Royle was used as a biotemplate to synthesize a CdS photocatalyst. The as-synthesized sample had the microstructure of nano-scaled aggregate networks and its activity for photocatalytic hydrogen production was six times higher than that of CdS synthesized without a template in an Na2S-Na2SO3 sacrificial system. The use of Pt and PdS as cocatalysts further improved the hydrogen production rate to 14.86 mmol/g·h under visible-light (λ ≥ 420 nm) irradiation, so the hydrogen production can be directly observed by the naked eye. The results of characterization showed that the as-synthesized CdS photocatalyst has a high specific surface area and narrow band gap, which is favorable for light absorption and photocatalytic reaction. This work provides a new way to search for efficient visible-light catalysts and confirms the uniqueness of a biotemplated synthesis method in obtaining specially structured materials.